Study of passively stable, fully detached divertor plasma regimes attained in innovative long-legged divertor configurations. (30th October 2019) - Umansky, M.V.; LaBombard, B.; Brunner, D.; Golfinopoulos, T.; Kuang, A.Q.; Rensink, M.E.; Terry, J.L.; Wigram, M.; Whyte, D.G.
Abstract: Numerical modeling of divertor configurations with radially or vertically extended, tightly baffled, outer divertor legs has demonstrated the existence of a passively-stable fully detached divertor regime. In the simulations, long-legged divertors provide up to an order-of-magnitude increase in peak power handling capability compared to conventional divertors. The key physics for attaining the passively stable, fully detached regime in these simulations involves the interplay of strong convective plasma transport to the divertor leg outer sidewall, confinement of neutral gas in the divertor volume, geometric effects including a secondary X-point, and atomic radiation. New analysis shows that in this regime the detachment front location is set by the balance between the power entering the divertor leg and the losses to the walls of the divertor channel. Correspondingly, the maximum power that can be accommodated by the divertor, while still staying detached, increases with the poloidal length of the leg. The detached regime access window in terms of input power, density and impurity seeding concentration varies quantitatively depending on divertor geometry and modeling assumptions most specifically, cross-field transport to the side walls.